2013
DOI: 10.1111/iep.12010
|View full text |Cite
|
Sign up to set email alerts
|

Canine visceral leishmaniasis as a systemic fibrotic disease

Abstract: We propose that canine visceral leishmaniasis (CVL) is a systemic fibrotic disease, as evidenced by the wide distribution of fibrosis that we have found in the dogs suffering from chronic condition. The inflammatory cells apparently direct fibrosis formation. Twenty-four cases (symptomatic dogs) were identified from a total of one hundred and five cases that had been naturally infected with Leishmania chagasi and had been documented during an epidemiological survey of CVL carried out by the metropolitan area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 46 publications
7
26
0
6
Order By: Relevance
“…Ao comparar os dados deste analito entre os diferentes grupos constatou-se diferença estatística significativa entre os animais classificados como sintomáticos e assintomáticos (Tabela 1). A hipoalbuminemia pode estar relacionada ao hipercatabolismo proteico, a lesão renal, a desnutrição e/ou ao defeito na síntese hepática decorrente da inflamação do fígado mediada pela resposta imune em pacientes com leishmaniose e já foi correlacionada a maior frequência de óbitos em pacientes humanos (Solano-Gallego et al, 2009, Silva et al, 2013.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Ao comparar os dados deste analito entre os diferentes grupos constatou-se diferença estatística significativa entre os animais classificados como sintomáticos e assintomáticos (Tabela 1). A hipoalbuminemia pode estar relacionada ao hipercatabolismo proteico, a lesão renal, a desnutrição e/ou ao defeito na síntese hepática decorrente da inflamação do fígado mediada pela resposta imune em pacientes com leishmaniose e já foi correlacionada a maior frequência de óbitos em pacientes humanos (Solano-Gallego et al, 2009, Silva et al, 2013.…”
Section: Methodsunclassified
“…Os tecidos cutâneo, renal e cardíaco são os mais frequentemente acometidos (Silva et al, 2013, Godoy et al, 2016. Contudo, o envolvimento do fígado, manifestado por hepatomegalia é considerado comum nos casos de leishmaniose visceral com manifestações como icterícia, hipoalbuminemia, fibrose, colestase (Valladares et al, 1997, Melo et al, 2009, Medeiros et al, 2010.…”
Section: Introductionunclassified
“…Visceral leishmaniasis in human beings and dogs is a systemic chronic inflammatory disease that promotes extracellular interstitial matrix (ECM) alterations. These alterations are mainly formed by collagen deposition (fibrosis) as a consequence of this visceral inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations are mainly formed by collagen deposition (fibrosis) as a consequence of this visceral inflammation. In fact, some studies have shown a direct association between fibrosis and Leishmania infection .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation